2007
DOI: 10.1021/ac0621726
|View full text |Cite
|
Sign up to set email alerts
|

Method for Label-Free Detection of Femtogram Quantities of Biologics in Flowing Liquid Samples

Abstract: Rapid (∼10 min) measurement of very low concentration of pathogens (∼10 cells/mL) and protein (∼fg/mL) has widespread use in medical diagnostics, monitoring biothreat agents, and in a broader context as a research method. For low-level pathogen, we currently use culture enrichment methods and, thus, rapid analysis is not possible. For low protein concentration, no direct method is currently available. We report here a novel macrocantilever design whose high-order resonant mode near 1 MHz exhibits mass detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 58 publications
1
82
0
Order By: Relevance
“…Until now, with few exceptions [22,23,172], there have been very few studies on in situ detection of proteins in aqueous environments. Here, in situ detection of proteins in solution is of high significance, because in situ detection allows the real-time monitoring of protein-protein interactions, which will enable novel insights into the kinetics of protein-protein interactions.…”
Section: Protein Detectionmentioning
confidence: 99%
“…Until now, with few exceptions [22,23,172], there have been very few studies on in situ detection of proteins in aqueous environments. Here, in situ detection of proteins in solution is of high significance, because in situ detection allows the real-time monitoring of protein-protein interactions, which will enable novel insights into the kinetics of protein-protein interactions.…”
Section: Protein Detectionmentioning
confidence: 99%
“…Ilic et al (2001) first reported the detection of single Escherichia coli (EC) cells using a cantilever array vibrating in vacuum. Maraldo et al (2007) extended the work of Ilic and co-workers, developing a composite, self-excited lead zirconate titanate (PZT)-glass millimeters size cantilever coated with anti-EC antibodies to detect the pathogen, EC O157:H7. They recently obtained impressive sensitivities for measurements both in buffered salt solutions (10 cfu/mL) and ground beef (100 cfu/mL).…”
Section: Introductionmentioning
confidence: 95%
“…We fitted P r (Fig. 4(a)) with an exponential function of the form P r t pol HT = P r0 + P r 1 − exp −t pol /t s400 (1) Here P r0 is the remnant polarization value before poling, P r the maximum achievable change in remnant polarization by the polarization process, and t s400 the time constant for poling with a dc poling field of 400 kV/cm. We obtain the fitting parameters as given in Table II for the SG(001) and the Text(001) films.…”
Section: The Poling Processmentioning
confidence: 99%
“…Sensing and actuation capabilities in most of the MEMS devices utilize the piezoelectric effect, such as in bio-sensors, [1][2][3] micro-machined ultrasonic transducers (MUTs), 4 5 accelerometers 6 resonators, 7 and micro-pumps. 8 9 Among piezoelectric thin-film materials, Pb(Zr x , Ti 1−x O 3 (PZT) films can offer an attractive option for piezoMEMS technology due to their superior ferroelectric and piezoelectric properties, and moreover, ease of integration into microsystems.…”
Section: Introductionmentioning
confidence: 99%